Figura mitologicznej Kasandry w filmach science fiction - Rojek, Patrycja (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2021)
The article reflects on how characters with the features of the mythological Cassandra function in science fiction films. Such references are part of the rich tradition of building fictional depictions of the near or distant future on the foundation of mythical stories. The study aimed to examine the considerable and complex meaning which Cassandra conveys through the ages and to determine its usefulness in constructing pop culture ideas about the current condition of humanity. In contemporary fiction, Cassandra is brought to the fore more often than in ancient sources, and her fullest portrait is drawn in those films that both consider her a figure of the powerlessness of the prophets and take into account her personal drama. In Terminator 2: Judgment Day (1991) by James Cameron, 12 Monkeys (1995) by Terry Gilliam, Minority Report (2002) by Steven Spielberg, and Arrival (2016) by Denis Villeneuve, the figure of Cassandra is examined through her prophetic gift, the alleged madness of the seer and the fearfulness of the prophetism itself.